Deterministic diffusion - Nizhnik, I. L.; Nizhnik, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.938In this paper, we present a series of definitions and properties of lifting dynamical systems (LDS) corresponding to the notion of deterministic diffusion. We give heuristic explanations of the mechanism of formation of deterministic diffusion in LDS and the anomalous deterministic diffusion in the case of transportation in long billiard channels with spatially periodic structures and nonideal reflection law.The expressions for the coefficient of deterministic diffusion are obtained.